STRATEGI PENGEMBANGAN DESTINASI WISATA PANTAI PULAU DATOK UNTUK MENINGKATKAN SOSIAL EKONOMI MASYARAKAT DESA SUTERA - Heriansyah Heriansyah; Sri Buwono; Putri Tipa Anasi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis study aims to determine the potential for attractions, accessibility, andamenities, the development of Datok Island coastal tourism on the socio-economic conditions of the community, and the appropriate strategy to beapplied. Descriptive research method with a qualitative approach. Dataobtained through observation, interviews, documentation and SWOT analysis.The results of the study showed potential attractions, namely white sand, hills,mangrove forests, the Karimata strait sail monument, the Dutch heritage pond.Accessibility is the condition of the road that has been paved. Amenity, namely,there are already built facilities such as gazebos, lodging and others. Theproblem of attractions is that there is no cultural tourism and lack of supportingattractions. There is no map or map of the beach location for accessibility.Amenity lack of facilities. The social economic level of education around thecoast is mostly elementary to junior high. The strategy is to develop otherpotentials such as cultural tourism (customs, handicrafts, arts and others),human potential (local cultural arts dance performances), building adequateinfrastructure facilities (souvenir shops, rides for games, sports venues, foodstalls). traders who are clean and tidy, make maps or plans for the location ofthe Datok island beach, carry out socialization of the development of good andcorrect tourist destinations, form POKDARWIS groups, conduct comparativestudies with more advanced tourist objects, promote maximum tourism objects,and empower all the community around the coast of Datok Island to promotelocal business.Keywords: Strategy, Tourism Destination Development, Social Economic